2010
DOI: 10.1099/ijs.0.003699-0
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of Geobacillus pallidus (Scholz et al. 1988) Banat et al. 2004 as Aeribacillus pallidus gen. nov., comb. nov.

Abstract: Although Anoxybacillus and Geobacillus, two genera of thermophilic bacteria close to the genus Bacillus, have only been described recently, the number of species in these genera has increased rapidly. Four thermophilic, lipolytic strains (DR01, DR02, DR03 and DR04) isolated from a hot spring in Veracruz (Mexico), which could not be identified phenotypically, were subjected to 16S rRNA gene sequence analysis. Three strains were identified as belonging to the genus Anoxybacillus, but strain DR03 was identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 21 publications
4
44
0
2
Order By: Relevance
“…Different species of the genus Geobacillus are also frequently identified as contaminants of dairy powders and inhabitants of dairypowder production facilities (Ronimus et al, 2003). Aeribacillus pallidus (formerly known as Geobacillus pallidus; Miñana-Galbis et al, 2010) has also been reported as a dominant species, in dairy powders, that produces highly thermoresistant spores (Lücking et al, 2013). These bacterial contaminants are generally regarded as hygiene indicators, and only a small part of them can cause actual product defect.…”
Section: Taxonomic Phenotypic and Genotypic Diversity Of Isolate Sementioning
confidence: 98%
“…Different species of the genus Geobacillus are also frequently identified as contaminants of dairy powders and inhabitants of dairypowder production facilities (Ronimus et al, 2003). Aeribacillus pallidus (formerly known as Geobacillus pallidus; Miñana-Galbis et al, 2010) has also been reported as a dominant species, in dairy powders, that produces highly thermoresistant spores (Lücking et al, 2013). These bacterial contaminants are generally regarded as hygiene indicators, and only a small part of them can cause actual product defect.…”
Section: Taxonomic Phenotypic and Genotypic Diversity Of Isolate Sementioning
confidence: 98%
“…Donor skin and burn margin were enriched with several taxa in comparison to control skin, including Aeribacillus ( p <0.005 and p <0.03, respectively), Caldalkalibacillus , ( p <0.02 and p <0.02, respectively) and Nesterenkonia ( p <0.004 and p <0.0007, respectively). These taxa are similar in that they are extremophiles, specifically thermophilic or halophilic (2123), and have not been extensively associated or studied in the context of pathogenesis in humans. In contrast, Corynebacterium , a widespread skin commensal, was significantly lower in both donor skin and burn margin relative to control skin ( p <0.001 and p <0.02, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The 16S rDNA sequence analysis revealed that the isolate YM-1 (HQ637544) had 100% homology with A. pallidus NCCP-131 (AB543491). The isolate YM-1 was Gram positive, spore forming with rod cells and was confirmed as A. pallidus (Bodour et al 2003;Minana-Galbis et al 2010;Mnif et al 2011).…”
Section: Identification and Phylogenetic Analysis Of The Bacteriamentioning
confidence: 99%